A Comparison Between the Effectiveness of Tepurak Therapy Versus Deep Tissue Massage Stretching on Low Back Function in Nonspecific Low Back Pain - Delano, Enggista Hendriko; Kushartanti, Wara; Arovah, Novita Intan; Shafi, Sabda Hussain As; Nugroho, Wahyu Aji (International Journal of Therapeutic Massage & Bodywork, 2024)
Introduction: The research carried out is a large research project that examined two different massage methods on many variables so that they can determine their effect on variables on a wider scale, namely pain, range of movement (ROM), and low back function. Pain and ROM variables have been published in different journals, and their acute effects are only known after treatment and the results are effective. This study examined the low back function variable 24, 48, and 72 hours after treatment. Objective: This study aimed to determine the effectiveness of Tepurak and deep tissue massaging with stretching (DTMS) on low back function in nonspecific low back pain (NSLBP) and conduct a comparison of the effectiveness of Tepurak versus DTMS for low back function in NSLBP. Methods: This research is a quasi-experiment using a pre-test/post-test design to determine the difference in scores before and after treatment. The variable measured involved the low back function using the Oswestry Disability Index. Measurements were carried out four times at pre-test, 24, 48, and 72 hours after the treatments. This study used two different sample groups. The research sample consisted of 42 NSLBP sufferers who were randomly divided into two groups, A and B. Group A received Tepurak treatment, while Group B received DTMS treatment. These treatments were carried out in one treatment session. Results: The results of the different treatments for the low back function variables in the Tepurak treatment have a p-value of 0.000. The results of the low back function variables in the DTMS treatment have a p-value of 0.000. The results of the comparison test of Tepurak versus DTMS therapy for the low back function variable had a p-value of 0.771. Conclusion: Both Tepurak and DTMS are effective in improving low back function in NSLBP cases. In comparison between Tepurak and DTMS, there was no significant difference in the effectiveness in improving low back function in NSLBP cases.